2013
DOI: 10.3892/mmr.2013.1629
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of pyridoxal stimulate the expression of IGFBP1 in HepG2 cells through upregulation of the ERK/c-Jun pathway

Abstract: Abstract. Increasing evidence suggests that dietary vitamin B6 is linked to the prevention of cancer and cardiovascular disease. However, the molecular mechanisms involved in this process are not yet understood. Preliminary results in the current study indicated, following DNA microarray analysis and quantitative PCR, that insulin-like growth factor-binding protein 1 (IGFBP1) mRNA is upregulated in HT29 colon carcinoma cells exposed to pyridoxal (PL, 500 µM). IGFBP1 is secreted from the liver and is hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Furthermore, among the 20 most regulated genes in microarray analysis (Table S2) IGFBP1 (upregulated by 8-fold in RG7388 resistant cells) was the most promising candidate due to the strongest reliability of confirmation by qRT-PCR (Supplementary Fig. S6A) and immunoblot analysis (Fig 2E) as well as based on literature research demonstrating a cross-link with the ERK1/2 pathway (34,35). In addition, microarray analysis showed an activation of the p53 pathway in RG7388-resistant cells, which was also seen in GSEA ( Fig.…”
Section: Resistance Against Rg7388 Treatmentmentioning
confidence: 93%
“…Furthermore, among the 20 most regulated genes in microarray analysis (Table S2) IGFBP1 (upregulated by 8-fold in RG7388 resistant cells) was the most promising candidate due to the strongest reliability of confirmation by qRT-PCR (Supplementary Fig. S6A) and immunoblot analysis (Fig 2E) as well as based on literature research demonstrating a cross-link with the ERK1/2 pathway (34,35). In addition, microarray analysis showed an activation of the p53 pathway in RG7388-resistant cells, which was also seen in GSEA ( Fig.…”
Section: Resistance Against Rg7388 Treatmentmentioning
confidence: 93%
“…On the other hand, other B 6 -vitamers including PLP, PN and PM had no such effect on p21 mRNA expression. We recently found that PL remarkably increases IGFBP1 mRNA whereas no other B 6 -vitamers have a similar effect (11). PL can freely pass through the cell membrane, and only PL is reported to interact with the cell surface of RAW264.7 cells cultured in culture medium treated with B 6 -vitamers (i.e., PL, PM, PN and PLP) (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence from in vitro and in vivo studies suggests p21 and p53 suppress cell proliferation (2,11,(19)(20)(21)(22)(23)(24)(25). In addition, p21 protects against oxidative stress (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It upregulates a protective factor, insulin like growth factor binding protein 1 (IGFBP1); its mRNA is upregulated in HT29 colon carcinoma cells exposed to pyridoxal (a form of vitamin B6). IGFBP1 is secreted from the liver and is hypothesized to exert a protective role in the development of cancer and cardiovascular diseases [20]. ELISA indicated analysis showed that supplemental vitamin B6 significantly lowered levels of colonic HSP70, heme-oxygenase-1, and HSP32 which increase cell proliferation and colonic damage.…”
Section: Discussionmentioning
confidence: 99%